Historical Linguistics 2011 : selected papers from the 20th International Conference on Historical Linguistics, Osaka, 25-30 July 2011 - Kikusawa, Ritsuko; Reid, Lawrence Andrew (Amsterdam studies in the theory and history of linguistic science. Current issues in linguistic theory ;, 2013)
Starting from Sapir's (1921) concept of linguistic "drift", this chapter explores long-term morphosyntactic change in Ancient Egyptian, with particular attention to the typological shift from agglutinative-synthetic to largely analytic morphological structure. The momentum for the continuing and pervasive analyticization process is to be sought in the profusion of a broad range of auxiliary verb constructions. The flipside of the drift towards analyticity is the decreasing morphological productivity of synthetic inflectional patterns. The structurally marked features of the Coptic particle sys